2013
DOI: 10.5507/fot.2013.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular species discovery in the diatom Sellaphora and its congruence with mating trials.

Abstract: Many diatom and other microbial eukaryote morphospecies consist of a variable number of (pseudo)cryptic species, with obvious consequences for such fields as biogeography and community ecology. Here, we investigated the species limits of morphologically similar small-celled strains of the model diatom Sellaphora from the United Kingdom and Australia, using cox1 mitochondrial and rbcL chloroplast gene sequences. Based on cox1 sequence data, the sequenced strains belonged to six closely related lineages, presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…commun., and Vanormelingen et al. ), and considerably greater than between putative species of N. palea , some of which have been shown to be reproductively isolated (Trobajo et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…commun., and Vanormelingen et al. ), and considerably greater than between putative species of N. palea , some of which have been shown to be reproductively isolated (Trobajo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of recent molecular studies have revealed cryptic diversity, suggesting that diatom biodiversity has been greatly underestimated (Mann and Vanormelingen 2013). For example, genetically distinct entities have been found within morphologically circumscribed species in Asterionellopsis (Kaczmarska et al 2014), Berkeleya (Hamsher and Saunders 2014), Chaetoceros (Huseby et al 2012;Kooistra et al 2010), Cyclotella (Beszteri et al 2005(Beszteri et al , 2007, Cylindrotheca (Vanormelingen et al 2013b), Eunotia (Vanormelingen et al 2008), Frustulia (Vesel a et al 2012), Gomphonema (Kermarrec et al 2013), Hantzschia (Souffreau et al 2012), Navicula (Cr each et al 2006;Poul ı ckov a et al 2010;Vanelslander et al 2009), Nitzschia ), Pinnularia (Souffreau et al 2012), Pseudo-nitzschia (Amato et al 2007), Sellaphora Vanormelingen et al 2013a), Skeletonema (Kaeriyama et al 2011;Kooistra et al 2008;Saravanan and Godhe 2010), and Tabularia (Kaczmarska et al 2009). However, the functional significance of this cryptic diversity is still unclear because studies on the physiology, ecology or geographical distributions of cryptic and pseudocryptic species are still relatively scarce.…”
mentioning
confidence: 99%
“…We tested the suitability of the 76bp metabarcode to assess proper phylogenetic distances within genera by comparing pairwise distances of reference sequences covering the short (76bp) and three longer rbcL fragments (1398bp, 939bp and 365bp). The 1398bp rbcL fragment have been successfully used to recover phylogenetic relationships in the genus Sellaphora (Evans et al, ; Vanormelingen, Evans, Chepurnov, Vyverman, & Mann, ) and a slightly shorter fragment was used to demonstrate phylogenetic relationships in Aulacoseira (Edgar & Theriot, ). Restricted by the available reference sequences, we could test intrageneric distances in 4 genera ( Sellaphora , Nitzschia , Navicula and Cyclotella ) by comparing the 1398bp and the 76bp rbcL barcode.…”
Section: Methodsmentioning
confidence: 99%
“…, Vanormelingen et al. ). Appropriate short regions within selected genetic markers can be used as “DNA barcodes” for identification (e.g., Mann et al.…”
mentioning
confidence: 99%